2016
DOI: 10.1186/s40691-016-0076-7
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and sustainable apparel retail models: does consumers’ tendency for creative choice counter-conformity matter in sustainability?

Abstract: The purpose of this study is to identify the relationships between consumer’s tendency for creative choice counter-conformity (TCCC) with the acceptance of new sustainable apparel retail models, including sale of redesigned clothing, clothing repair/alteration, renting, swapping, and style consultancy services, in addition to determining the role of demographics in the relationships. Three major hypotheses were developed to address these relationships. An online survey was conducted with 431 females in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The emphasis on closing the loop and circularity [69] (external drivers), and equity, authenticity, functionality, localism, and exclusivity [19] (internal drivers) seems to be the drivers setting the discussion in the paper analyzed apart from the previously identified drivers in the academic literature (see Tables 5 and 6). Sustainable consumption is the result in both Lang et al [68] and Pedersen and Andersen's [70] research where sustainable products are discussed, such as redesigning garments and the increasing interest among consumers for renting new clothes, and re-using, repairing, and up-cycling fashion garments. This is in line with the Ellen MacArthur Foundation [15] emphasis on circularity and partly with the SCP cycle [47], as presented in Figure 3.…”
Section: Value Creation Xmentioning
confidence: 99%
See 2 more Smart Citations
“…The emphasis on closing the loop and circularity [69] (external drivers), and equity, authenticity, functionality, localism, and exclusivity [19] (internal drivers) seems to be the drivers setting the discussion in the paper analyzed apart from the previously identified drivers in the academic literature (see Tables 5 and 6). Sustainable consumption is the result in both Lang et al [68] and Pedersen and Andersen's [70] research where sustainable products are discussed, such as redesigning garments and the increasing interest among consumers for renting new clothes, and re-using, repairing, and up-cycling fashion garments. This is in line with the Ellen MacArthur Foundation [15] emphasis on circularity and partly with the SCP cycle [47], as presented in Figure 3.…”
Section: Value Creation Xmentioning
confidence: 99%
“…The topic of the sixth article written by Lang, Armstrong, and Liu [68] discuss sustainable consumption and sustainable apparel retail models. The objective was to identify the relationship between consumer "Tendency for Creative Choice Conformity (TCCC) and the acceptance of newly sustainable apparel retail models" (p. 1) focusing on sales, redesigning, repairing, renting, and swapping of products, as well as consultant services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lin and Huang [59] and Biswas and Roy [11] support this hypothesis, stating that novelty seeking represents one of the main reasons that customers choose to purchase green and eco-friendly products. Although green products are usually more expensive and of a lower quality than non-green products [31], survey-based data obtained from 431 female customers in the United States [60] revealed that the consumer's tendency to make creative choices enhances their adoption of new and sustainable retail products. Thus, this study hypothesizes the following:…”
Section: The Context Of the Studymentioning
confidence: 99%
“…However, given the aim of this research, the RBV has been found as a suitable approach because this study only focuses on the internal aspects of fashion firms that implement PSS, which is greatly needed since previous research on fashion PSS is mainly concerned with consumer adoption [27,[113][114][115]. Taking a RBV on HRM has the advantage to provide a clear structure of internal HR components that are critical for a firm's success and, therefore, serves as an ideal framework to identify, compare and analyze different HRM elements.…”
Section: People Management Systemsmentioning
confidence: 99%